1985
DOI: 10.1073/pnas.82.20.6755
|View full text |Cite
|
Sign up to set email alerts
|

Modification of chromium(VI)-induced DNA damage by glutathione and cytochromes P-450 in chicken embryo hepatocytes.

Abstract: The role ofglutathione and cytochrome P-450 in the production of DNA damage by chromium(VI) was examined In chicken embryo hepatocytes by the alkaline elution technique. Cellular levels of glutathione and cytochrome P-450 were altered by treating the hepatocytes with N-acetyl-Lcysteine, buthionine sulfoximine, isopentanol, or 8-naphthoflavone. A dramatic increase in chromium(VI)-induced DNA strand breaks was observed after increasing glutathione levels in the cells. Chromium(VI)-induced DNA strand breaks were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 27 publications
1
51
0
Order By: Relevance
“…[3]) manganese(I1) has a slight catalytic effect on the reaction, but when that ratio equals 7 the effect of that ion is inhibitory instead, and the inhibition observed is more intense as the reductantloxidant ratio increases. Actually, manganese(I1) ion is known to be an inhibitor for many chromium(V1) redox reactions, due to its ability to act as a trapping agent for the intermediate chromium (1V) (17); however, the maximum decrease in the reaction rate that can be expected from this effect is 50% (9), and for a reductantloxidant ratio > 34 we have observed that the inhibitory effect of manganese(I1) ion on the chromium(VI)/~~-PA reaction exceeds that limit (and it would be probably larger at higher values of the reductantloxidant ratio).…”
Section: Mechanism In the Presence Of Manganese(i1) Ionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3]) manganese(I1) has a slight catalytic effect on the reaction, but when that ratio equals 7 the effect of that ion is inhibitory instead, and the inhibition observed is more intense as the reductantloxidant ratio increases. Actually, manganese(I1) ion is known to be an inhibitor for many chromium(V1) redox reactions, due to its ability to act as a trapping agent for the intermediate chromium (1V) (17); however, the maximum decrease in the reaction rate that can be expected from this effect is 50% (9), and for a reductantloxidant ratio > 34 we have observed that the inhibitory effect of manganese(I1) ion on the chromium(VI)/~~-PA reaction exceeds that limit (and it would be probably larger at higher values of the reductantloxidant ratio).…”
Section: Mechanism In the Presence Of Manganese(i1) Ionmentioning
confidence: 99%
“…More recently, some interest has arisen on the kinetics and mechanism of this and similar reactions at physiological pH, since it seems probable that the mutagenic effects of the well-known carcinogen chromium(V1) require its previous reduction inside the cell, and glutathione and other biological thiols seem to b e likely candidates as reductants (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Cr(V) complexes have been reported to induce DNA breakage and %hydroxy-2'-deoxyguanosine in vitro as well as mutation in bacterial systems, and recent in vitro studies indicated that not only Cr(VI)/(V) but also the Cr(III)/ (II) redox couple serve as cyclical electron donors, in a Fenton-like reaction, to produce active oxygen species [5-81. Among the biological reductants, GSH has been reported to be present normally in millimolar concentrations in intact cells, and the modification of cellular GSH in cultured cells has been shown to alter the levels of DNA damage caused by Cr(VI) [9]. Furthermore, ESR studies have shown that Cr(II1) and Cr(V) complexes are formed during reduction of Cr(V1) by GSH in vitro, and *Corresponding author.…”
mentioning
confidence: 99%
“…However, it is not clear why these vitamins have an ability to change the chromium(V) but not the chromium(III) complex in cells. With respect to DNA damage, DNA breaks induced by chromate have been reported to be associated with cellular levels of glutathione and the activity of cytochrome P-450 reductase, whereas protein crosslinks were not dependent upon these factors (12). Furthermore, our previous studies have shown that in three different cell lines of human, mouse, and hamster origin, the order of sensitivity to DNA-protein crosslinks was not consistent with the sensitivity to formation of DNA breaks by chromate (8), suggesting that chromium-induced DNA-protein crosslinks may be formed by a different mechanism than that for single-strand breaks.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the cellular metabolism of chromium(VI) may play a role in the induction of chromate toxicity and carcinogenicity. Chromium(VI) compounds have been shown to produce DNA single-strand breaks and DNA-protein crosslinks (3,(6)(7)(8)(9)(10)(11)(12) and to selectively inhibit the activity of glutathione reductase (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%